High throughput screening against the peroxidase cascade of African trypanosomes identifies antiparasitic compounds that inactivate Tryparedoxin - Füller, Florian; Krauth-Siegel, Renate (The journal of biological chemistry, 2012)
In African trypanosomes, the detoxification of broad spectrum hydroperoxides relies on a unique cascade composed of trypanothione (T(SH)2), trypanothione reductase, tryparedoxin (Tpx), and nonselenium glutathione peroxidase-type enzymes. All three proteins are essential for Trypanosoma brucei. Here, we subjected the complete system to a high throughput screening approach with nearly 80,000 chemicals. Twelve compounds inhibited the peroxidase system. All but one carried chloroalkyl substituents. The detailed kinetic analysis showed that two compounds weakly inhibited trypanothione reductase, but none of them specifically interacted with the peroxidase. They proved to be time-dependent inhibitors of Tpx-modifying Cys-40, the first cysteine of its active site WCPPC motif. Importantly, gel shift assays verified Tpx as a target in the intact parasites. T(SH)2, present in the in vitro assays and in the cells in high molar excess, did not interfere with Tpx inactivation. The compounds inhibited the proliferation of bloodstream T. brucei with EC50 values down to <1 μm and exerted up to 83-fold lower toxicity toward HeLa cells. Irreversible inhibitors are traditionally regarded as unfavorable. However, a large number of antimicrobials and anticancer therapeutics acts covalently with their target protein. The compounds identified here also interacted with recombinant human thioredoxin, a distant relative of Tpx. This finding might even be exploited for thioredoxin-based anticancer drug development approaches reported recently. The fact that the T(SH)2/Tpx couple occupies a central position within the trypanosomal thiol metabolism and delivers electrons also for the synthesis of DNA precursors renders the parasite-specific oxidoreductase an attractive drug target molecule.
Gesehen am 01.06.2018